2011
DOI: 10.1167/iovs.11-7989
|View full text |Cite
|
Sign up to set email alerts
|

The TAg-RB Murine Retinoblastoma Cell of Origin Has Immunohistochemical Features of Differentiated Müller Glia with Progenitor Properties

Abstract: TAg-RB tumors displayed molecular similarity to human retinoblastoma and origin in a cell with features of differentiated Müller glia with progenitor properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…4 Moreover, we have never observed overlap between TAg and cone opsin or RXR␥ staining (Pajovic S, unpublished data, 2010), but have shown overlap with multiple cell markers that clearly demonstrated that the cell of origin in this model possesses features of differentiated Müller glia with progenitor properties. 2 Although timing of pRB inactivation in our model makes it "not surprising that the cells stain for maturing progenitors," what is interesting is that inactivation of pRB at this time and in this unique cell type produces a tumor with significant similarity to human retinoblastoma, regardless of whether it originates from the same cell type.…”
Section: Madhavan and Khetanmentioning
confidence: 88%
See 2 more Smart Citations
“…4 Moreover, we have never observed overlap between TAg and cone opsin or RXR␥ staining (Pajovic S, unpublished data, 2010), but have shown overlap with multiple cell markers that clearly demonstrated that the cell of origin in this model possesses features of differentiated Müller glia with progenitor properties. 2 Although timing of pRB inactivation in our model makes it "not surprising that the cells stain for maturing progenitors," what is interesting is that inactivation of pRB at this time and in this unique cell type produces a tumor with significant similarity to human retinoblastoma, regardless of whether it originates from the same cell type.…”
Section: Madhavan and Khetanmentioning
confidence: 88%
“…2 First, we reiterate that it is not possible to draw direct conclusions about the cell of origin of human retinoblastoma on the basis of data in the TAg-RB mouse model; unfortunately, we lack the unambiguous marker of the tumor lineage in human retinoblastoma that TAg provides in the mouse. Second, the timing of RB1 loss in humans does not coincide with the developmental period in which TAg is activated in TAg-RB.…”
Section: Madhavan and Khetanmentioning
confidence: 97%
See 1 more Smart Citation
“…The early stages of tumor development in the Tag model were investigated by Pajovic et al [7] by tracking Tag protein expression in the retina. The SV40 Tag causes neoplastic transformation of the developing retinal cells.…”
mentioning
confidence: 99%
“…We read with interest a recent paper by Pajovic et al, 1 on the TAg-RB murine retinoblastoma cell of origin. We would like the authors to answer a few queries that may help us to understand the work better.…”
mentioning
confidence: 99%